2023
DOI: 10.1111/1365-2435.14477
|View full text |Cite
|
Sign up to set email alerts
|

Herbaceous species and dry forest species have more acquisitive leaf traits than woody species and wet forest species

Tomonari Matsuo,
Masha T. van der Sande,
Lucy Amissah
et al.

Abstract: Life forms are key to understand the changes in species composition and vegetation types in space and with succession over time. We asked how life forms from dry and wet regions differ in their leaf traits and trait hyperspace (i.e. trait variation) in early tropical forest succession on abandoned agricultural fields. We compared 324 early successional species from six life forms (herbs, grasses, vines, lianas, shrubs and trees) that occur in the first 5 years of succession on abandoned fields in Ghanaian wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Plant absorption of mobile nutrients is directly proportional to root hair length because soil nutrients more easily reach the roots with greater root hair lengths (Bates and Lynch, 2001;Evans, 2012). For woody plants, by contrast, we only observed that root hair length was positively related to soil K. These results indicate that morphological traits of the root hairs of herbaceous plants were more closely related (Bibikova and Gilroy, 2002;Matsuo et al, 2023). Specifically, herbaceous plants depend primarily on root proliferation for resource foraging, while woody plants depend mainly on mycorrhizal foraging (Michael, 2001;Tawaraya, 2003;Golivets et al, 2024).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Plant absorption of mobile nutrients is directly proportional to root hair length because soil nutrients more easily reach the roots with greater root hair lengths (Bates and Lynch, 2001;Evans, 2012). For woody plants, by contrast, we only observed that root hair length was positively related to soil K. These results indicate that morphological traits of the root hairs of herbaceous plants were more closely related (Bibikova and Gilroy, 2002;Matsuo et al, 2023). Specifically, herbaceous plants depend primarily on root proliferation for resource foraging, while woody plants depend mainly on mycorrhizal foraging (Michael, 2001;Tawaraya, 2003;Golivets et al, 2024).…”
Section: Discussionmentioning
confidence: 59%
“…On the other hand, herbaceous plants have shallower root systems compared with woody plants ( Van der Waal et al, 2009;Wang et al, 2023;Golivets et al, 2024). The vertical distribution of the root system is directly related to their efficiency in absorbing soil resources (Matsuo et al, 2023). Consequently, woody plants are subjected to more nutrient stress than herbaceous plants (Wang et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, understory plants must have a strong light capture capacity to meet their growth requirements. Therefore, during the transition, plants with smaller specific leaf area and thicker leaves are better adapted to the increased solar radiation and reduced water availability ( Matsuo et al., 2024 ) ( Supplementary Figures 1 and 2 ). Forest and grassland possess elevated functional diversity, a broad variety of species traits, and more comprehensive resource utilization in comparison to the transition zone.…”
Section: Discussionmentioning
confidence: 99%
“…The trend of FDis and RaoQ was consistent, higher in grassland than in other locations (Figures 3G, H). These findings suggest that plant species in grassland exhibit a greater degree of trait differentiation and ecological niche differentiation, leading to more efficient resource utilization and relatively weaker competition, resulting in higher productivity (Mason et al, 2005).In the transition zone, the variation in CWM.H reflects the regular spatial distribution of plants. This distribution effectively reduces runoff and maintains soil nutrients necessary for plant growth.…”
Section: Characteristics Of Plant Diversity and Ecological Functions ...mentioning
confidence: 90%